(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2022)
The study of foreign languages in modern society has become an inseparable component of the training of specialists at all levels. The article undertakes a brief review of private methods of teaching foreign language communicative competence of students.